A Versatile Strategy for Surface Functionalization of Hydrophobic Nanoparticle by Boronic Acid Modified Polymerizable Diacetylene Derivatives - Gu, Shiwei; Guo, Chang; Wang, Hui; Tian, Guangjun; Xu, Suying; Wang, Leyu (Frontiers in Chemistry, 2019)
The flourishing advancements in nanotechnology significantly boost their application in biomedical fields. Whereas, inorganic nanomaterials are normally prepared and capped with hydrophobic ligands, which require essential surface modification to increase their biocompatibility and endow extra functions. Phenylboronic acid derivatives have long been known for its capacity for selective recognition of saccharides. Herein, we demonstrated a versatile surface modification strategy to directly convert hydrophobic inorganic nanocrystals into water-dispersible and targeting nanocomposites by employing boronic acid modified photo-polymerizable 10,12-pentacosadiynoicacid and further explore its potentials in selective cancer cell imaging.